The Implications of Digital Transformation and Its Impact on Human Resource Management Strategies - Hasan Abdulsalam Ali Emran; Fathia .M. Elhony (East Asian Journal of Multidisciplinary Research, 2023)
The application of digitization in organizations requires attention to refining the skills of human resources and increasing their knowledge to achieve organizational goals efficiently. This study aims to identify the impact of digital transformation on human resource management strategies, particularly in the education sector where the shift from traditional to digital education has caused significant changes. Sustainable development is also a challenge facing the world, and this study explores how digital transformation affects human resource management strategies. The study used a descriptive analytical approach and surveyed 37 administrative leaders at the University of Fezzan. The results show a significant impact of digital transformation on human resources management strategies, highlighting the need for organizations to adapt and introduce technology in their systems to achieve sustainable development goals.